The Influence Of Marketing Strategy And The Use Of E-Commerce Technology On Improving Business Performance From A Sharia Perspective: A Case Study Culinary Industry (Umkm) In Medan City - Dongoran, Rahmah Nur; Ridwan, M; Syahriza, Rahmi (UNIVERSITAS PAKUAN, 2025)
Micro Small and Medium Enterprises (UMKM) play a strategic role in the Indonesian economy, particularly in the rapidly growing culinary sector in Medan. This study aims to analyze the influence of marketing strategies and the use of e-commerce technology on the business performance of culinary, using Sharia principles as a moderating variable. The research method used a quantitative approach with multiple regression analysis, simultaneous (F) tests, partial (t) tests, and Moderated Regression Analysis (MRA). The results indicate that marketing strategies and e-commerce have a significant positive effect on business performance. Furthermore, Sharia principles have been shown to strengthen this relationship, emphasizing the importance of integrating Islamic values in the digitalization of UMKM. This study provides academic contributions to the development of Sharia economics literature and provides practical guidance for culinary UMKM in increasing their competitiveness and sustainability.